Dissolved oxygen shapes the archaeal communities in the seawater of Changjiang Estuary - Wang, Jianxin; Tian, Chunmiao; Wu, Dongmei; Wang, Rixin (Frontiers in Environmental Science, 2023)
Archaea play a significant role in regulating the biogeochemical processes of marine ecosystems. In this study, the high-throughput sequencing was used to explore the archaeal communities in the seawater from the hypoxic and non-hypoxic zones of the Changjiang Estuary. Thaumarchaeota dominated the archaeal communities in the hypoxic zones (bottom water), and Euryarchaeota were mainly distributed in the non-hypoxic zones (surface water). However, the diversity and richness of the archaeal communities showed no obvious difference in the hypoxic and non-hypoxic zones. Moreover, Thaumarchaeota and Nitrosopumilales were positively correlated with salinity, but negatively correlated with dissolved oxygen (DO) and temperature. Temperature, phosphorus, and dissolved oxygen had significant correlations with archaeal richness, while ammonia nitrogen was correlated with archaeal diversity. The networks of archaeal communities possessed a high proportion of positive interspecific interaction and revealed that the Marine Group II species may play distinct roles in both hypoxic and non-hypoxic zones. The current work assessed the influence of dissolved oxygen on the archaeal community patterns and network interaction, thereby illumining the community structure shift of archaea caused by the hypoxia phenomenon in the Changjiang Estuary, which laid a foundation for the future studies on the ecological functions of archaea in estuary ecosystems.